Whitehead and Eurhthmic Becoming: The Forgotten Ontology of Rhythms (Nóema, 2020)
In the debate on the philosophical foundations of physics, Whitehead's philosophy of organism plays an essential role. Despite the efforts made by many scholars, Whitehead's realistic stance invalidates any attempt to relate his philosophy to either the Copenhagen's and the orthodox interpretation of quantum mechanics. In both his earlier mathematical works and his successive philosophical ones his «constructive task» was «a protest against exempting any part of the universe from change». Whitehead aimed to melt his expertise in mathematical logic and in mathematical physics in order to get both an axiomatic and a cosmological frame different from the Newtonian: the notion of field, first introduced by electromagnetism, is not reconcilable with the mechanist image of the world; still, both in relativity and quantum theory, non-linear phenomena have shown the limits of applicability of classical postulates. The symbolic formalization carried on by Whitehead has as exemplifying counter-side the ontological notion of rhythm, one common to both micro- middle- and macro-scales. A quanta of energy, as well as a molecule of iron, a music note, a biological organism, an ocean tide, a planet and a star are periodical systems that need some “lapse of time” for functioning, for manifest themselves as entities and for express their individuality. Each of these systems have «to be conceived as modifications of conditions within space-time, extending throughout its whole range». Moreover, these periodically, rhythmically pulsing systems, these «states of agitation» are analyzable in a «focal region» and in an external, but not separated stream, since «for physics, the thing itself is what it does, and what it does is this divergent stream of influence».
Keywords: Realism; Whitehead's Complexity Ontology; Rhythms and Patterns; Events and Objects; Quantum Theory and Relativity Theory